Analysis of Soundness Level in the CAMELS Ratio Perspective - Muh. Syaukin Muttaqin; Sindy Marchelia Putri; Siti Rumilah (Majapahit Journal of Islamic Finance and Management, 2021)
Banks in a country have an important role. One of its functions is as a financial intermediary whose operations are for the community. The soundness of banks and their stability are very important because they affect the ups and downs of an economy. It can foster public trust because people are increasingly selective in choosing financial institutions. Bank Syariah Mandiri is the bank with the highest total assets compared to other Islamic banks. The purpose of the study was to determine the level of soundness at Bank Syariah Mandiri during the 2017-2019 period using the CAMELS ratio. The results show that the soundness of Bank Syariah Mandiri Syariah, even though it has a greater total assets than other Islamic banks, is still not in the very healthy category because from the research results, Bank Mandiri Syariah is currently in the healthy category. However, on the sensitivity risk assessment, Bank Syariah Mandiri is in the very healthy category.